Doctor Death and Coronavirus: Supplicating Santa Muerte for Holy Healing - Kingsbury, Kate (Anthropologica, 2021)
Human beings have long turned to religion and faith healing to overcome illness and seek to delay death. In the context of the COVID‑19 pandemic, I consider how in Mexico, devotees of Santa Muerte are turning to the folk saint of death to ward off and recover from the virus. I argue that supplication of Santa Muerte during times of coronavirus offers a social critique on the current context in Mexico. The government has introduced budget cuts, reducing spending during this pandemic, and failed to provide adequate measures to protect already vulnerable citizens living in poverty and within the grips of the drug war, from COVID‑19. Frontline workers are labouring in unsafe conditions with inadequate protective equipment and protocols. As a result, the death toll has risen rapidly. Mexico is currently listed as having the fourth highest death rate. I describe how fearing death, many have turned to the saint of death for recovery from coronavirus and to prolong life. My argument also counters the popular portrayal of Santa Muerte as a narcosaint, that is to say a saint solely venerated by narcotraffickers. Instead, I reveal that she is a saint of healing.